A taste of their own medicine: Guideline adherence and access to expertise - Finkelstein, Amy et al (The American Economic Review: Insights)
We use administrative data from Sweden to study adherence to 63 medication-related guidelines. We compare the adherence of patients without personal access to medical expertise to that of patients with access, namely doctors and their close relatives. We estimate that observably similar patients with access to expertise have 3.8 percentage points lower adherence, relative to a baseline adherence rate of 54.4 percent among those without access. Our findings suggest an important role in nonadherence for factors other than those, such as ignorance, poor communication, and complexity, that would be expected to diminish with access to expertise.